The buffalo are back - George, Jean Craighead, 1919-2012.; Minor, Wendell (New York : Dutton Children's Books, 2010)
Presents an environmental success story of the buffalo's return from near extinction that describes the contributions of the Native Americans, cowboys, and Teddy Roosevelt as well as the rebuilding of herds in national parks.
Includes bibliographical references.
Sequoyah Nominee 2013
800
Keywords: American bison; American bison -- History; Endangered species -- United States; Great Plains -- Environmental aspects